The psychological adjustment of middle managers after revolutionary organisational change - Coates, Nicholas Robert (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
With the accelerated process of political and socio-economic transformation in South Africa, revolutionary organisational change has become a given in contemporary South African business life (Human & Horwitz, 1992). For revolutionary organisational change to succeed in South Africa, middle managers who represent the 'cement' of the organisation, need to adjust at the individual level. However, the literature on organisational change remains curiously silent about individual adjustment (Ashford, 1988). The goals of the research were firstly, to recount the middle manager's perceptions and experiences of revolutionary organisational change. Secondly, to detail the psychological re-<lrientation and reidentification of middle managers within their 'changed' organisational context. Thirdly, to understand the relative success of middle managers' psychological adjustment. A single case study design was most appropriate as the study represented a unique case in that it was the most transformed public organisation in South Africa. An initial research group and two theoretically relevant sub-groups were created through theoretical sampling. The data collected through in-depth interviews, direct observation and documentation, and the analysis of this data were jointly undertaken. The results indicate that the respondents perceived a necessity for revolutionary organisational change due to the political changes within South Africa. However, the actual management of the change process was perceived to be poor as the respondent's experienced a lack of participation and a lack of communication. The traumatic 'side effects' of these experiences included feelings of powerlessness and uncertainty which increased the level of organisational stress. Specific individual differences proved largely ineffective in moderating the increased stress. This was attributed to the violation of the individual respondents' psychological contract and the subsequent shared psychological disorientation. The violation resulted in feelings of hurt, betrayal and resentment which shifted the respondents view of the employment relationship. The respondents were therefore unable to identify with the 'new' organisation. This was evident in their attitudinal and behavioural responses which included a lack of trust, lack of organisational commitment and a shift in work satisfaction as weU as ensuing 'offsetting' behaviour and a reluctance to engage in organisational citizenship behaviour. These attitudinal and behavioural responses strongly suggested that the respondents' psychological adjustment was predominantly ineffectual.
Keywords: Psychology, Industrial -- South Africa; Organizational change -- South Africa; Organizational change -- Psychological aspects; Management -- Psychological aspects